The changing character of the work of art: the mona lisa from the perspective of historicism - Ribeiro, Roney Jesus (Revista do Colóquio, 2023)
In this article we intend to explore ideas concerning historicism, an important concept for understanding historical facts from the philosophy of history. Historicism is made up of a set of doctrines that is not limited to a ready-made definition. There are many ways to understand these doctrines. To understand this historical perspective, we adopted the method of artistic interpretation, starting from the analysis of Mona Lisa (1503), by Leonardo da Vinci and reinterpretations produced by modern and contemporary artists inspired by the aforementioned work. With this article, we aim to investigate the changing character of the work of art from the perspective of historicism. As the work of art is an open circuit, it is subject to resignifications at each historical moment. In this sense, historicism, a philosophical doctrine, can contribute to understanding the meanings of a work of art over time.